2011
DOI: 10.5390/susb.2011.2.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Thermal Mass to Energy Performance of Buildings: A Comparative Analysis

Abstract: Concrete has structural, architectural, and environmental applications in buildings. As one of its advantages, the thermal mass property of concrete plays an important role in a building's energy performance and reduces heating and cooling loads. In this paper, results of an investigation of the effect of thermal mass of concrete on a building's energy consumption in comparison with steel and masonry are presented. For the purpose of this research, three major parameters including height, occupancy, and locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…For instance, wooden exterior walls may have one-third of the active thermal mass in comparison to brick or concrete walls, depending on the composition. This difference may result in an increased space heat and cooling demand. The influence of thermal mass on the heat balance depends on several factors, such as the climatic conditions at the building location . For example, Aste et al found differences in space heat demand of about 10%, while Dodoo et al reported only a minor increase of approximately 2%. , Despite the increased operational energy associated with wood as a construction material, it often displays a reduced environmental impact over its entire life cycle, depending on the end-of-life scenario. , Evidently, a tradeoff between material choice and building energy demand exists.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, wooden exterior walls may have one-third of the active thermal mass in comparison to brick or concrete walls, depending on the composition. This difference may result in an increased space heat and cooling demand. The influence of thermal mass on the heat balance depends on several factors, such as the climatic conditions at the building location . For example, Aste et al found differences in space heat demand of about 10%, while Dodoo et al reported only a minor increase of approximately 2%. , Despite the increased operational energy associated with wood as a construction material, it often displays a reduced environmental impact over its entire life cycle, depending on the end-of-life scenario. , Evidently, a tradeoff between material choice and building energy demand exists.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it could be assumed that in a typical application, it would not significantly affect the thermal behaviour. The dynamic DV model is able to predict within reasonable accuracy the thermal behaviour of typical buildings where the only relatively small active thickness of the structure interacts with the regularly varied heat gains (Johannesson 1981;Ghoreishi and Ali 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that using thermal mass decreased the heating loads by as much as 47%, whereas a slight increase of cooling loads was observed. Moreover, a recent study conducted by Ghoreishi and Ali (2011) has shown that concrete thermal mass on average could save 7 to 10% of annual cooling energy consumptions for both office and residential occupancies in different U.S. climate zones.…”
Section: Thermal Mass and Energy Performancementioning
confidence: 98%
“…There are several factors that can affect the thermal mass behavior of concrete, including thermal diffusivity, heat capacity, building insulation, outside daily temperature swings, and the building design and operation (Ghoreishi and Ali 2011).…”
Section: Benefits Of Thermal Massmentioning
confidence: 99%